Allelopathic effect of aqueous extract of Ageratum conyzoides on seed germination and seedling growth of brassicaceae vegetables - Mustapha, Nur Fatin Qairawani (2015)
Allelopathy is the suppression of growth, development, and distribution of nearby plants and microorganisms caused by the release of toxic compounds called allelochemicals by plants which grow dominantly in an area such as Ageratum conyzoides. Thus, a study was conducted to determine the allelopathic potential of Ageratum conyzoides on seed germination and seedling growth of three Brassicaceae vegetables, Brassica juncea (mustard green), Brassica alboglabra (kailan), and Lactuca sativa (lettuce). Ten percent of aqueous extracts of roots, stems, leaves and flowers of Ageratum conyzoides were used to treat the seeds of the three vegetables on filter paper in Petri-dishes. Seed germination was counted after 10 days and seedling radicle and plumule length was measured at every three days interval starting from the first day of germination until 15th day as an indicator of allelopathy of Ageratum conyzoides. The experiment was conducted in Completely Randomized Design (CRD) with five replications. Aqueous extract of Ageratum conyzoides did not affect seed germination of the three Brassicaceae vegetables. However, the extracts affected the seedling growth of these vegetables on their shoot and root development. Extracts from leaf and stem produced the highest inhibitory effects on the seedling growth of the vegetables by 25-50%, followed by the effect from flower and root extract with 0-30%. Ageratum conyzoides plants produce allelopathic chemicals. Different parts of plant produce significant difference of allelopathic phenomenon on seedling development of the three Brassicaceae vegetables. Extract from leaf and stem cause higher inhibitory effect on shoot and root development of Brassicaceae vegetables seedling, more than those from flower and root.